(untitled) (Global Journal of Medical Research, 2023)
Background Pregnancy is a critical stage in a woman life and the use of drugs especially antibiotics calls for concern The service and choice of antibiotics during pregnancy depends mainly on maternal factors such as health nutrition and socio-economic status as well as the mode of delivery This study was aimed to assess antibiotic use among pregnant women according to the Food and Drug Administration categorization of drugs based on their risk in pregnancy Methods The study was a retrospective cross-sectional survey The sampling consisted of all prescriptions for pregnant women with at least one antibiotic drug and recorded in a registry